The role of data in transformations to sustainability: a critical research agenda - Albuquerque, João Porto de; Anderson, Liana; Calvillo, Nerea; Coaffee, Jon; Cunha, Maria Alexandra; Degrossi, Livia Castro; Dolif, Giovanni; Horita, Flavio; Klonner, Carolin; Lima-Silva, Fernanda; Marchezini, Victor; Martins, Mario Henrique da Mata; et al. (Current opinion in environmental sustainability, 2021)
This article investigates the role of digital technologies and data innovations, such as big data and citizen-generated data, to enable transformations to sustainability. We reviewed recent literature in this area and identified that the most prevailing assumption of work is related to the capacity of data to inform decision-making and support transformations. However, there is a lack of critical investigation on the concrete pathways for this to happen. We present a framework that identifies scales and potential pathways on how data generation, circulation and usage can enable transformations to sustainability. This framework expands the perspective on the role and functions of data, and it is used to outline a critical research agenda for future work that fully considers the socio-cultural contexts and practices through which data may effectively support transformative pathways to sustainable development.